2008
DOI: 10.1158/0008-5472.can-07-6614
|View full text |Cite
|
Sign up to set email alerts
|

Targeting V600EB-Raf and Akt3 Using Nanoliposomal-Small Interfering RNA Inhibits Cutaneous Melanocytic Lesion Development

Abstract: Most events promoting early melanoma development are yet to be identified but deregulation of the B-Raf and Akt3 signaling cascades are important regulators of this process. Approximately 90% of normal moles and ~60% of early invasive cutaneous melanomas contain a T1799A B-Raf mutation (V600EB-Raf), leading to 10X higher enzyme activity and constitutive activation of the MAP kinase pathway. Furthermore, ~70% of melanomas have elevated Akt3 signaling due to increased gene copy number and PTEN loss. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
154
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(160 citation statements)
references
References 42 publications
2
154
0
4
Order By: Relevance
“…Historically, researchers have relied on physicochemical methods to facilitate epidermal penetration and cellular delivery of negatively charged nucleic acids (11,(30)(31)(32)(33). However, these methods require high concentrations of free siRNAs, can have unacceptable toxicity in in vivo models, and are limited by the instability of conventional siRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, researchers have relied on physicochemical methods to facilitate epidermal penetration and cellular delivery of negatively charged nucleic acids (11,(30)(31)(32)(33). However, these methods require high concentrations of free siRNAs, can have unacceptable toxicity in in vivo models, and are limited by the instability of conventional siRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the small treated areas showed a marked reduction in skin thickening, the pain and the impracticality associated with these injections made the approach untenable. Other mechanical approaches, such as ultrasound and laser, have been used to facilitate penetration through the mouse stratum corneum and drive siRNA into skin, but require specialized equipment (30,31,33), limit the area of delivery, and can potentially harm the skin. Recent investigations have demonstrated uptake of siRNAs and DNAs into the epidermis in mice with no stratum corneum (e.g., open wounds or mucosae) or with atopic dermatitis, an inflammatory skin disorder with an ineffective epidermal barrier (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that PI3K and MEK inhibitors synergise to reduce growth and survival of melanoma cell lines grown under 3D organotypic cell culture conditions Meier et al, 2007). There is also evidence that siRNA knockdown of AKT3 and BRAF V600E leads to the enhanced inhibition of melanoma xenograft growth in nude mice Tran et al, 2008). …”
Section: Suitable Combination Targets: the Pi3k Pathway?mentioning
confidence: 97%
“…Furthermore, the increase in Akt3 activity in their melanoma model was associated with both Akt3 gene amplification and mutations in PTEN (104). Subsequently, data from the Robertson group (42,105) demonstrated a direct link between tumor progression in melanoma cells with Akt3-dependent phosphorylation of B-RAF.…”
Section: Akt3 and Melanomamentioning
confidence: 98%